The new art and science of teaching mathematics - Lang-Raad, Nathan D. (Solution Tree Press, 2019)
"In The New Art and Science of Teaching Mathematics, authors Nathan D. Lang-Raad and Robert J. Marzano describe, in detail, how the New Art and Science of Teaching model should be used in the mathematics classroom. Recognizing that the New Art system was originally created as a general model of instruction, the authors adapt the model to the instruction of mathematics in order to address how instruction changes in a particular subject area. Thus, the authors explain each of the ten design areas and the forty-three elements of instruction within those design areas originally laid out in Robert Marzano's The New Art and Science of Teaching, as well as how they should be addressed in the mathematics classroom. In addition to explanation of the design areas, the authors also provide numerous strategies and methods for implementation that mathematics instructors will find invaluable in their own use of the New Art model in the classroom. In this book, readers will find a detailed and well-researched guide to the implementation of the New Art model of instruction that will allow them to pursue implementation of improved student outcomes"--